(untitled) (Research, Society and Development, 2023)
Background and objectives: Child sexual violence is one of the causes of higher morbidity and mortality in Brazil and in the world. Considered a traumatic experience in childhood or adolescence that reflects in acts for a lifetime, both physical and psychological, seen by society as transgressors of children’s rights. This study aims to characterize the profile of sexual violence against children and adolescents in the state of Pará from 2017 to 2020, comprising the historical period related to the Covid-19 pandemic and its grievance on the subject. Methods: This is a retrospective descriptive observational study, and used as a source data extracted from the Health Information System of the Department of Informatics of the Unified Health System (DATASUS) under public consultation and research of studies in the database. Results: During the study period, there were 6,154 notifications, with a decrease occurring during the isolation period. The most vulnerable victims are between 10 and 14 years old (59%), predominantly female (87.8%). The profiles of aggressors that stood out were friends/acquaintances and family members such as stepfather, with the victims’ residence being the most common place of occurrence. Conclusion: Recognizing the determinants of child sexual violence is essential for the implementation of comprehensive care actions for victims. It is necessary to sensitize health managers and train teams so that comprehensive health care for children and adolescents in situations of violence is continuous and permanent.